Perpetuum Mobile of Radicalism – Islamism in la France Laïque - Mariusz Sulkowski (Chrześcijaństwo-Świat-Polityka)
The article points to growing cultural tensions in France today. On the one hand, the French government is tightening the rules of laïcité, while on the other, Islam is playing an increasingly important role. This is due to both the consolidation of Muslim identity and the ever-growing Muslim population in France. According to the author, French republicanism, which is inextricably linked to laïcité, is incapable of resolving this tension and, in fact, systemically generates it.